Effects of CNT inclusions on structure and dielectric properties of PVDF/CNT nanocomposites. (2nd August 2016) - Kripotou, Sotiria; Sovatzoglou, Spyridon; Pandis, Christos; Kuliček, Jaroslav; Mičušík, Matej; Omastova, Maria; Kyritsis, Apostolos; Konsta, Amalia; Pissis, Polycarpos
ABSTRACT: The effects of multiwall carbon nanotube (CNT) inclusions on the crystalline structure of poly(vinylidene fluoride) (PVDF), and on the dielectric properties of PVDF/CNT nanocomposites (NCs), prepared by melt mixing, were investigated by employing X-ray diffraction, differential scanning calorimetry, and dielectric spectroscopy techniques. Our results imply that, in the NCs, the formation of β-phase crystals depends on specific compression treatment in the melt and fast cooling. Dielectric measurements on NCs, with CNT concentrations below the electrical percolation threshold, reveal that the dielectric strength of the two relaxation processes in the amorphous phase and dielectric permittivity, ϵ′, measured within the broad temperature range from −150 °C to 60 °C, increase strongly with increasing CNT concentration. This enhancement of amorphous PVDF polarizability has been attributed to the increase of the local electric field, due to local polarization generated at the surface of conductive inclusions/CNT clusters.